Modelagem da drenagem urbana e avaliação das cargas bacteriológicas na vertente marítima de Fortaleza, Ceará - Mesquita, Janine Brandão de Farias (2018)
Urban drainage systems can represent sources of pollutants to the receiving bodies for which they are intended, especially in densely populated coastal towns. Therefore, the present work aims to propose a tool for modeling the urban drainage system of the Vertente Marítima de Fortaleza basin, Ceará, aiming to evaluate the bacteriological loads. To this end, the following steps were followed: 1) Selection of the computational model, in this case, the Stormwater Management Model-SWMM for the hydrological and hydraulic simulations in the sub-basins; 2) Quantitative model validation with measured flow data in six sub-basins, using statistical analysis (calculation of the standard deviation and Nash-Sutcliffe-CNS coefficient of efficiency); 3) Proposition of the tool for calculation of bacteriological loads by estimating the diffuse load -CD per unit area (NMP, day-1.hectare-1) and its correlation with a series of environmental variables and 4) Scenario analysis for different conditions of precipitation, sewage collection and solid residues inadequately disposed of - RSDI. Field campaigns were also carried out to collect data from the SWMM, as well as the collection of water samples for analysis of the Escherichia coli parameter. The results of the work showed that the SWMM offers representative answers, the standard deviation between measured and modeled flows being less than 20% and the CNS higher than 0.90. Regarding the predictive model, a second order power function was adjusted by correlating CD (NMP, day-1.ha-1) with the mean monthly precipitation (mm.day-1) for the three sub-basins analyzed (R² = 0.972). Afterwards, the coefficients of the equations were correlated to the RSDI (Kg.dia-1) of the sub-basins, obtaining a logarithmic adjustment (R² = 0.997), with which it is possible to obtain an equation of estimate of CD for any basin of the Coastal Strand. The scenarios analysis showed a significant increase of the load in extreme rainfall events and a considerable decrease with the increase of the fraction of the population connected to the sewage network to the reduction of 50% of the RSDI production. It was concluded that the model was adequate to the Fortaleza reality and could be used as a practical tool to simulate the urban drainage and prediction of the tributary loads to the coastal zone of the city. It is hoped that the proposed methodology may also be applied in other cities with hydro-environmental characteristics similar to Fortaleza.